Quality of work life and associated factors among health professionals working at private and government health institutions in Awi zone, Amhara regional state, Ethiopia, 2022: a comparative cross-sectional study - Ayalew, Agumas Fentahun; Ma, Wei; Tamir, Workineh; Mitiku, Kefale (Frontiers in Public Health, 2024)
Background: Quality of work-life issues significantly impact the economic, physical, and psychological well-being of health professionals and their families. Enhancing QWL aims to foster a conducive environment and improve work performance. This study evaluated the quality of work life of health professionals in government and private health institutions in the Awi zone, Ethiopia.Methods: A comparative cross-sectional approach was employed, with study participants selected via the lottery method in 2022. Socio-demographic and organizational-related data were collected, coded, cleaned, and entered into Epi-Data version 3.1, then analysed using SPSS version 27. Candidate variables were selected using bivariable logistic regression (pvalue < 0.20). We used multivariable logistic regression to identify factors associated with quality of work life, presenting AOR with a 95% CI at a 5% significance level. The results: The study included 385 private health professionals and 395 government health professionals, with response rates of 90.38% and 92.72%, respectively. Overall quality of work-life satisfaction was 53.08% (95% CI: 49.2-57.0), with private health institution workers reporting satisfaction at 42.3% (95% CI: 37.4-47.30) and government health professionals at 63.54% (95% CI: 58.78-68.31). The difference between the two groups was 21.2% (95% CI: 14.3, 27.9). Factors significantly associated with quality of work life included type of health institutions (AOR=2.272; 1.684, 3.065), family size (AOR=1.536; 1.122, 2.103), personnel protective equipment (AOR=1.369; 1.006, 1.863), eye protection (AOR=2.090; 1.514, 2.885), engineering control (AOR=1.563; 1.140, 2.143), and accessibility of alcohol (AOR=1.714; 1.219, 2.410).Health professionals in private health institutions exhibited lower quality of work-life satisfaction than government health institutions. Quality of work life was significantly associated with the type of health institutions, family size, availability of personal protective equipment, eye protection, engineering control, and accessibility of alcohol. Regular monitoring and evaluation of the quality of work life, ensuring the availability of appropriate personal protective equipment, and providing sufficient materials and equipment for both groups were recommended based on the findings.